Increasment Public Awareness About the Importance of Waste Management Using the Reduce, Reuse and Recycle Methods in Preventing Environmental Pollution in Bora Village - Insarullah; Serdiati, Novalina; Muliati, Muliati; Edy, Nur (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
This activity aims to increase public awareness regarding the importance of managing waste using reduce, reuse and recycle methods. The implementation method starts from the introduction of the concept, the problem solving stage includes identifying possible factors that cause low community participation in waste management, obstacles in realizing increased public awareness in waste management, follow-up plans for identified problems, implementation forms of the solutions offered. and evaluation. The coaching stage is related to the implementation of waste management. The results of the implementation of activities where the community has understood the method and its application in managing waste that is around it according to its type. Increased public knowledge about how to reduce waste and its management to improve environmental quality. Socialization about waste management using reduce, reuse and recycle methods can increase community participation in minimizing the accumulation of waste around the living environment.